Calcium and vitamin-D deficiency marginally impairs fracture healing but aggravates posttraumatic bone loss in osteoporotic mice. Issue 1 (December 2017) - Fischer, Verena; Haffner-Luntzer, Melanie; Prystaz, Katja; vom Scheidt, Annika; Busse, Björn; Schinke, Thorsten; Amling, Michael; Ignatius, Anita
Abstract Calcium and vitamin-D (Ca/VitD) deficiency is a major risk factor for osteoporosis. It may also contribute to the compromised bone healing frequently observed in osteoporotic patients, since calcium is essential for fracture-callus mineralization. Additionally, clinical data suggest systemic bone loss following fracture, which may aggravate osteoporosis and thus increase the risk for fragility fractures in osteoporotic patients further. However, the role of Ca/VitD in fracture healing and posttraumatic bone turnover has to date been poorly investigated. Here, we studied bone regeneration and posttraumatic bone turnover in C57BL/6 J mice with ovariectomy-induced osteoporosis. Mice were fed a standard or a Ca/VitD-deficient diet. Notably, fracture healing was only marginally disturbed in Ca/VitD-deficient mice. However, deficient mice displayed significantly increased serum parathyroid hormone levels and osteoclast activity, as well as reduced bone mass in the intact skeleton post-fracture, suggesting considerably enhanced calcium mobilization from the intact skeleton during bone regeneration. Ca/VitD supplementation initiated post-fracture prevented posttraumatic bone loss by reducing bone resorption and furthermore improved bone repair. These results imply that adequate Ca/VitD supply post-fracture is essential to provide sufficient calcium for callus-mineralization in order to prevent posttraumatic bone loss and to reduce the risk for secondary fractures in osteoporotic patients with Ca/VitD deficiency.